Low‐acuity presentations to regional emergency departments: What is the issue?. (28th December 2015) - Cheek, Colleen; Allen, Penny; Shires, Lizzi; Parry, Denise; Ruigrok, Marielle
Abstract: Objective: To explore GP‐referrals and self‐referrals to EDs and factors associated with patients seeking low‐acuity care at ED. Method: Retrospective analysis of all ED presentations to Mersey Community Hospital and North West Regional Hospital (Tasmania) between 1 January 2009 and 31 December 2013. Cross‐sectional survey of patients presenting to the EDs for care triaged as low‐acuity. Results: There were 255 365 ED presentations in the retrospective data: 11 252 (4.4%) GP‐referrals and 218 205 (85.4%) self‐referrals. At ED 49% of GP‐referrals were triaged ATS 4 or 5 and 35% of self‐referrals were triaged ATS 1–3. There were 138 (84.2%) low‐acuity patients who completed the survey; predominantly, all attended for acute injury or illness. Single point‐of‐care convenience was most commonly selected (71%) as a reason for attending ED. Conclusions: Over 85% of patients who seek emergency care in this region self‐refer, so understanding health‐seeking behaviour is important. Most low‐acuity patients are acutely injured or unwell, and the decision to go to ED is based on their perception of accessibility of expertise aligned with their need. The term 'GP‐type' is misleading in this context and should not be used. Providing low‐acuity care in parallel with providing a specialised emergency service meets the needs of the local community and is likely to be the lowest cost model in a regional and rural area. Funding models must reflect the actual cost of delivering this important service rather than presentation types.